Influence of Tip Diameter and Light Spectrum of Curing Units on the Properties of Bulk-Fill Resin Composites - Cardoso, Igor Oliveiros; Machado, Alexandre Coelho; Fernandes, Luísa de Oliveira; Soares, Paulo Vinícius; Raposo, Luís Henrique Araújo (European Journal of Dentistry, 2021)
Objective The aim of this study was to evaluate the influence of different light-curing units (LCUs) with distinct tip diameters and light spectra for activating bulk-fill resins.Materials and Methods The specimens (n = 10) were made from a conventional composite (Amaris, VOCO) and bulk-fill resins (Aura Bulk Fill, SDI; Filtek One, 3M ESPE; Tetric Bulk Fill, Ivoclar Vivadent) with two diameters, 7 or 10 mm, × 2 mm thickness. Following 24 hours of specimen preparation, the degree of conversion (DC) was evaluated using the Fourier-transform infrared unit. Knoop hardness (KHN) readings were performed on the center and periphery of the specimens. Data were assessed for homoscedasticity and submitted to one-way and three-way analysis of variance followed by the Tukey's and Dunnett's tests, depending on the analysis performed (α = 0.05).Results LCUs and specimen diameter significantly affected the DC. The Tetric Bulk Fill provided increased DC results when light-cured with Valo (54.8 and 53.5%, for 7 and 10 mm, respectively) compared with Radii Xpert (52.1 and 52.9%, for 7 and 10 mm, respectively). No significant differences in KHN results were noted for the conventional resin composite (Amaris) compared with LCUs (p = 0.213) or disc diameters (p = 0.587), but the center of the specimen exhibited superior KHN (p ≤ 0.001) than the periphery.Conclusion The light spectrum of the multipeak LCU (Valo) significantly increased the DC and KHN of the bulk-fill resin composite with additional initiator to camphorquinone (Tetric Bulk Fill) compared with the monowave LCU (Radii Xpert). The tip size of the LCUs influenced the performance of some of the resin composites tested.
Keywords: resin composite; light curing; polymerization